Application of SYSML on a simplified model of an air surveillance radar - Jevtić, Miloš D.; Marinković, Siniša R.; Marjanović, Ivica B. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Systems Modeling Language (SysML) is a Unified Modeling Language (UML) profile intended for application in systems engineering. This text is inspired by lack of literature on SysML in Serbian language. Its goal is to introduce this interesting modeling language to the engineering and academic community, with a special emphasis on the differences from UML. An overview is given, using an original example – a simplified model of an air surveillance radar. A short analysis of practical aspects of SysML is made – its scope of acceptance, the prospects of its further application, etc. We concluded that SysML is a useful, accepted and promising modeling language.